2004
DOI: 10.1902/jop.2004.75.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐11 and IL‐17 and the Pathogenesis of Periodontal Disease

Abstract: Gingival concentrations of IL-11 and IL-17 are different in diseased gingiva adjacent to 3, 4 to 5, and > or = 6 mm pockets, suggesting that their concentrations change as a consequence of the progression of gingivitis to periodontitis and that both cytokines could have a significant role in this progression. These data may be useful for the design of procedures for prevention of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
157
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(177 citation statements)
references
References 53 publications
15
157
0
5
Order By: Relevance
“…In vitro studies have reported that treatment of healthy human periodontal ligament cells with lipopolysaccharide (LPS) from inflammatory pathogens involved in perio-http://bmbreports.org BMB reports dontal disease stimulates IL-6 release (56). Local expression of IL-6 at periodontic sites is higher than levels in similar sites in healthy controls (57,58). Surprisingly however, periodontal lesions induced by pulp exposure were larger in IL-6 null mice than wild type, but this model does not involve infection (59).…”
Section: Gp130 and Periodontal Diseasementioning
confidence: 84%
See 1 more Smart Citation
“…In vitro studies have reported that treatment of healthy human periodontal ligament cells with lipopolysaccharide (LPS) from inflammatory pathogens involved in perio-http://bmbreports.org BMB reports dontal disease stimulates IL-6 release (56). Local expression of IL-6 at periodontic sites is higher than levels in similar sites in healthy controls (57,58). Surprisingly however, periodontal lesions induced by pulp exposure were larger in IL-6 null mice than wild type, but this model does not involve infection (59).…”
Section: Gp130 and Periodontal Diseasementioning
confidence: 84%
“…OSM has also been detected at high levels in periodontal endothelial and inflammatory cells (60), in gingival fluid (61) and in the circulation of patients with chronic periodontal disease (62), but is not observed in these locations in healthy subjects, suggesting that OSM may contribute to ongoing pathogenesis in this condition. In contrast, local expression of IL-11 is high in pockets of gingivitis (early stage periodontitis), but is low in established chronic periodontitis, suggesting a role for IL-11 in disease establishment only (58). No involvement of CT-1, CNTF or LIF in periodontal disease has been reported.…”
Section: Gp130 and Periodontal Diseasementioning
confidence: 98%
“…IL-11 induces bronchial inflammation (35,36), and it is induced by respiratory viral infections (37,38). Parallel increases in the IL-11 and IL-17 gene expression have been demonstrated in the animal model of rheumatoid arthritis (39), in inflammatory periodontal disease (40), and in the gastrointestinal mucosal Th17 cell inflammatory infiltrate associated with IL-11/STAT3 overexpression (29). The chromosomal region containing the IL-11 gene (19q13) has been associated with susceptibility to MS (41); however, its role in the development of the inflammatory response in MS has not been elucidated.…”
mentioning
confidence: 96%
“…This cytokine is found at elevated levels in many inflammatory conditions in humans, particularly rheumatoid arthritis and lung airway infections (reviewed in Refs. 4 -7), but also Heliobacter pylori infection (8), multiple sclerosis (9), periodontal disease (10,11), and psoriasis (12). Mice deficient in the IL-17R also show an impaired ability to recover from Klebsiella pneumoniae infections (13).…”
mentioning
confidence: 99%